Implementasi Penggunaan Smartphone Android untuk Control PC (Personal Computer) - Imam Solikin (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
The purpose of this research is to simplify the control of personal computer (PC) such as control pointer, keyboard control and make it easier to do the presentation by controlling the slide remotely using smartphone through wifi connections facility. The smartphone is a multimedia phone that combines PC functionality with microprocessor, memory, and built-in modem to produce smart smartphone gadgets. Problems that occur when performing a presentation such as PC control, control pointer and keyboard control for input should be close to the PC so it is less than optimal in explaining the material. The model used in implementing the use of Android Smartphone for PC control is a conceptual model consisting of several stages: potential and problems, data collection, system testing, test results, and system implementation or implementation. From the results of PC control research can be done by connecting the Smartphone with a PC via wifi network so that PC can be controlled remotely. PC control application is an application that can control PC remotely connected via wifi network connection. Benefits derived from this research make it easy to mengedalikan PC remotely such as facilitate in the percentage and control pointer and control Keyboard for input process.